The effect of management practices in intensive prawn culture on the organic matter level of the water ways, province of North Sumatra, Indonesia - Hamid, Azwar (College of Fisheries, University of the Philippines, 1991)
The effect of management practices in intensive prawn culture system on the organic matter level of the waterways of North Sumatra (Indonesia) was assessed February 7, 1991 until August 6, 1991. This was made from 5 sampling periods and 3 sampling stations. Results show increasing trends in Biological Oxygen Demand, phytoplankton density, soil sedimentation, Carbon/Nitrogen (%), Nitrogen total (%), Phoshorus-available, potential acidity and acetate soluble sulfate ; and decreasing trends in iro-available, and Aluminum-exchangeable ions over time. Correlations of these parameters and the two pond management practices (feeding rates and water exchange) show trends of highly significant adverse effect on the environment.